A novel mode of induction of the humoral innate immune response in Drosophila larvae - Hiroyuki Kenmoku; Aki Hori; Takayuki Kuraishi; Shoichiro Kurata (The Company of Biologists, 2017)
Drosophila adults have been utilized as a genetically tractable model organism to decipher the molecular mechanisms of humoral innate immune responses. In an effort to promote the utility of Drosophila larvae as an additional model system, in this study, we describe a novel aspect of an induction mechanism for innate immunity in these larvae. By using a fine tungsten needle created for manipulating semi-conductor devices, larvae were subjected to septic injury. However, although Toll pathway mutants were susceptible to infection with Gram-positive bacteria as had been shown for Drosophila adults, microbe clearance was not affected in the mutants. In addition, Drosophila larvae were found to be sensitive to mechanical stimuli with respect to the activation of a sterile humoral response. In particular, pinching with forceps to a degree that might cause minor damage to larval tissues could induce the expression of the antifungal peptide gene Drosomycin; notably, this induction was partially independent of the Toll and immune deficiency pathways. We therefore propose that Drosophila larvae might serve as a useful model to analyze the infectious and non-infectious inflammation that underlies various inflammatory diseases such as ischemia, atherosclerosis and cancer.